Servant Leadership Model Decrease Nurses’ Work Stress and Burnout - Euis Purwatyningsih; Giri Widakdo; Tri Widakdo (Fakultas Keperawatan Universitas Andalas, 2025)
Leadership plays an important role in influencing team member performance to achieve goals. The servant leadership model can create an adaptive and collaborative work environment, thus potentially reducing nurse stress and burnout. This study aims to identify the relationship between the servant leadership model of the ward head with work stress and burnout of nurses in the inpatient ward of Harapan Kita Children and Mother Hospital. This study used a cross-sectional design conducted in November-December 2024, including 128 nurses who worked in Harapan Kita Children and Mother Hospital. Data analysis was conducted using univariate descriptive analysis, bivariate chi-square test, and multivariate simple logistic regression test. The results showed a significant relationship between servant leadership and nurse work stress (ρ = 0.008, OR = 2.776) and with nurse burnout (ρ = 0.000, OR = 4.2). Multivariate analysis showed that servant leadership could reduce the incidence of nurse burnout by up to 5,588 times greater after being controlled by the variables of age, education, and length of service. The implementation of the ward head servant policy can help reduce nurse work stress and burnout, which has the potential to improve mutual care services in hospitals. Leadership training for head nurses and regular evaluations are needed to enhance servant leadership, foster a supportive work culture, improve nurse well-being, and elevate the quality of nursing care.